Factores socioculturales y prácticas de autocuidado en adultos con crisis hipertensiva - Sarachaga Gallardo, Milagros Eulojia (2023)
The present descriptive correlational research was carried out with the purpose of determining the relationship between sociocultural factors and self-care practices of adult patients with hypertensive crisis who attended Hospital I Moche, in a sample population of 64 patients, two instruments were used. ; a Survey on sociocultural factors and a Test to assess self-care practices in adult patients with hypertensive crisis, respecting ethical principles, for the relationship of the variables the Chi square statistical test was used, reaching the following results: 62, 5% of the patients were older than 60 years, while 4.7% were adults 18 to 39 years old; also 51.6% of male adults; 48.4% have completed secondary school and with a minimum percentage of 7.8% with incomplete primary and complete higher education; 54.7% are married, 7.8% single and divorced; 70.3% belong to the coast, while 9.4% comes from the jungle. 73.4% presented regular self-care practices, 15.6% good practices and only 10.9% low self-care practices; therefore, there are sociocultural factors that are related to the level of self-care practices in adult patients with hypertensive crisis, with age being p=0.029; the level of education with a p = 0.048 and the place of origin with a p = 0.043 (p < 0.05%)